2020
DOI: 10.1093/toxsci/kfaa136
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of hiPSC-Derived Neuronal Cocultures and Rodent Primary Cortical Cultures for In Vitro Seizure Liability Assessment

Abstract: Seizures are life-threatening adverse drug reactions which are investigated late in drug development using rodent models. Consequently, if seizures are detected, a lot of time, money and animals have been used. Thus, there is a need for in vitro screening models using human cells to circumvent inter-species translation. We assessed the suitability of co-cultures of human induced pluripotent stem cell (hiPSC)-derived neurons and astrocytes compared to rodent primary cortical cultures for in vitro seizure liabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 58 publications
(21 reference statements)
1
39
0
Order By: Relevance
“…Moreover, the first data from such systems did not provide strong evidence for a robust NMDA-R response. However, compounds acting on other glutamate receptors like domoic acid, have shown clear responses (Nimtz et al 2020 ; Tukker et al 2020 ). As MCCs can be generated relatively fast, and Ca 2+ imaging is performed in 96-well format, our system allows a sufficient throughput for small screens and relatively extensive follow-up characterizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the first data from such systems did not provide strong evidence for a robust NMDA-R response. However, compounds acting on other glutamate receptors like domoic acid, have shown clear responses (Nimtz et al 2020 ; Tukker et al 2020 ). As MCCs can be generated relatively fast, and Ca 2+ imaging is performed in 96-well format, our system allows a sufficient throughput for small screens and relatively extensive follow-up characterizations.…”
Section: Discussionmentioning
confidence: 99%
“…The hitherto most robust MEA data have been generated with rat primary neurons. More recently, murine and human-stem cell-derived neurons have been demonstrated to be principally suitable for the analysis of network signalling on MEA (Pagan-Diaz et al 2020 ; Tukker et al 2020 ). However, the production of cultures at a reasonable price, time effort and robustness has proven challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons derived from hiPSCs are amenable for long-term studies and highthroughput parallel screening for targeted drug discovery. Pairing with MEA, a highthroughput, extracellular recording assay of neuronal activity (Odawara et al, 2016) (Odawara et al, 2018Tukker et al, 2020b), study has shown a successful application of patient-specific disease modeling to discover epilepsy therapies (Tidball et al, 2020). Using the hiPSC-derived neurons, it was found that riluzole and phenytoin can target specific Nav1.6 variants to attenuate bursting phenotypes in vitro, and suppress patient seizure events in the clinical study (Tidball et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons derived from hiPSCs are amenable for high-throughput parallel screening for targeted drug discovery. Pairing with MEA, a high-throughput, extracellular recording assay of neuronal activity, 57,74,75 such studies have been attempted with neurons carrying Nav1.6 variants. 64 Using the hiPSC-derived neurons, it was recently found that riluzole and phenytoin can target specific Nav1.6 variants to attenuate bursting phenotypes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the availability of MEA data derived from human cells is still scarce. The sensitivity between cells from different species can differ, with rat cortical cultures being more sensitive to methoxetamine (Hondebrink et al., 2017), and, on the other hand, hiPSC‐derived neurons being more sensitive to several seizureogenic compounds (Tukker, Wijnolts, de Groot, & Westerink, 2020b). Notably, however, differences in sensitivity between cells from different species are generally small, i.e., less than a factor of 10 (Tukker et al., 2020b), or negligible (Kasteel & Westerink, 2017).…”
Section: Introductionmentioning
confidence: 99%